2022
DOI: 10.1021/acsnano.1c10750
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Patterning of In Vitro Neuronal Circuits

Abstract: Methods for patterning neurons in vitro have gradually improved and are used to investigate questions that are difficult to address in or ex vivo. Though these techniques guide axons between groups of neurons, multiscale control of neuronal connectivity, from circuits to synapses, is yet to be achieved in vitro. As studying neuronal circuits with synaptic resolution in vivo poses significant challenges, we present an in vitro alternative to validate biophysical and computational models. In this work we use a c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Cell engineering based on microfluidics has become an indispensable technology for studying structure-function relationships and modeling neuronal network functions in vitro , and the high-temporal resolution of the MEA, along with its potential to record LFPs, enables the analysis of novel aspects of the engineered networks. In addition to network modularity, precise control of axon orientation ( Peyrin et al, 2011 ) and even dendritic spines ( Mateus et al, 2022 ) has been demonstrated using microfluidic devices. Combination of such neuroengineering technology with state-of-the-art MEA devices will open new application of in vitro systems as a tool in fundamental neuroscience and pharmacology.…”
Section: Discussionmentioning
confidence: 99%
“…Cell engineering based on microfluidics has become an indispensable technology for studying structure-function relationships and modeling neuronal network functions in vitro , and the high-temporal resolution of the MEA, along with its potential to record LFPs, enables the analysis of novel aspects of the engineered networks. In addition to network modularity, precise control of axon orientation ( Peyrin et al, 2011 ) and even dendritic spines ( Mateus et al, 2022 ) has been demonstrated using microfluidic devices. Combination of such neuroengineering technology with state-of-the-art MEA devices will open new application of in vitro systems as a tool in fundamental neuroscience and pharmacology.…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, RFP-expressing iNeurons were used, allowing to visualize the neurons’ whole morphology. To get more information about the network’s connections, additional genetically encoded fluorescent markers could be added, for example to locate synapses using the presynaptic terminal marker PreSynTagMA and the postsynaptic marker PSD-95 (Mateus et al, 2022). This should make it possible to precisely link the structure and electrical functional activity of the network.…”
Section: Discussionmentioning
confidence: 99%
“…This chip can more accurately control the connection and topology of the neural network and ultimately form a fully accessible and connected neural microcircuit. [ 45 ] On most multichamber microfluidic chips, the chambers are connected in the same horizontal plane through microchannels, leading to the same horizontal separation of cell bodies and axons. This horizontal structure cannot fully simulate the 3D microenvironment in the brain.…”
Section: Key Technologies Of Boc Constructionmentioning
confidence: 99%